Old problems in the new solutions? Politically motivated allocation of program benefits and the "new" fertilizer subsidies - Banful, Afua Branoah (International Food Policy Research Institute, 2010)
Despite their disappointing performance in the recent past, fertilizer subsidies have re-emerged as a tool in the agricultural strategies of many countries in Sub-Saharan Africa. The new paradigm for fertilizer subsidies calls for use of such mechanisms as vouchers to target benefits to poor smallholders and public–private partnerships to develop private markets. There is some belief that with these innovations, fertilizer subsidy programs will circumvent the deleterious consequences of the programs of the past. However, there has been a glaring lack of innovation in how to prevent politics from dominating the allocation of subsidy program benefits and exacerbating inefficiencies as was the experience in earlier programs. This paper studies how vouchers, which could be used towards the purchase of fertilizer, were distributed amongst districts in Ghana's 2008 fertilizer subsidy program. We find that politics played a significant role in the allocation of vouchers. Higher numbers of vouchers were targeted to districts that the ruling party had lost in the previous presidential elections and more so in districts that had been lost by a higher margin. A district received 2 percent more vouchers for each percentage point by which the ruling party had lost the previous presidential election - this amount is both statistically and numerically significant. The analysis also shows that district poverty levels, which should have been an important consideration in an economic efficiency motivated distribution, were not a statistically significant determinant of districts' voucher allocation. The evidence that vouchers were targeted to areas in which the opposition party received strong support is suggestive of the vouchers being used for vote-buying. This finding raises the caution that despite innovations in implementing fertilizer subsidies, politically motivated allocation of subsidy benefits remains a major potential source of inefficiency.